1995
DOI: 10.1080/09670269500650871
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and distribution of species of the diatom genusSkeletonemain a tropical coastal lagoon

Abstract: Phytoplankton collected bimonthly by net during 1991-2 from the Sontecomapan lagoon (12 km long and 1"5 km wide), in the Gulf of Mexico, included four species and several forms of the diatom genus Ske]etonema. The spatial and temporal distribution of Skeletonema subsalsum, S. pseudocostatum and S. costatum in the lagoon varied with the salinity. S. subsa]sum was dominant in the rainy season (JulyFebruary), when salinity was 0-6 ppt. S. costatum was abundant in the adjacent marine zone, occasionally with S. tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The centric diatom genus Skeletonema occurs worldwide and often forms dense blooms in coastal regions (Karentz & Smayda, 1984;Ake´-Castillo et al, 1995;Huang et al, 2007). Traditionally, only a few species were recognized, based on morphological features recognizable in light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The centric diatom genus Skeletonema occurs worldwide and often forms dense blooms in coastal regions (Karentz & Smayda, 1984;Ake´-Castillo et al, 1995;Huang et al, 2007). Traditionally, only a few species were recognized, based on morphological features recognizable in light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…tropicum in Jiaozhou Bay decreased considerably after August, and result in low abundances, making the detection diffi cult. Castillo et al (1995) found that S . tropicum grows optimally at salinity above 29°C.…”
Section: The Cell Abundance and Distribution Of S Tropicum In The Jmentioning
confidence: 99%
“…tropicum and S . costatum (Ueno, 1993;Castillo et al, 1995;Sarno et al, 2005;Naik et al, 2010). Seawater (25 mL) of the mixed phytoplankton samples were taken and placed in a 25-mL glass chamber for cell numeration.…”
Section: Species Identifi Cation and Cell Numerationmentioning
confidence: 99%
See 2 more Smart Citations